الظاهرة الدينية عند ماكس فيبر - خيذر، جميلة (مؤسسة كنوز الحكمة للنشر والتوزيع, 2021)
سعت هذه الورقة البحثية إلى عرض الظاهرة الدينية عند عالم الاجتماع الألماني ماكس فيبر وتحليلها، وذلك نظرا إلى أنه قد درس مجموعة من العقائد والأديان. مثل: المسيحية في كتابه: الأخلاق البروتستانية وروح الرأسمالية، واليهودية في كتابه: اليهودية القديمة، والهندوسية والبوذية في كتابه: الهندوسية والبوذية، والكنفوشيوسية والطاوية في كتابه الموسوم ب: الكنفوشوسية والطاوية... إلخ. فحاولنا في البداية تقديم نبذة عن السيرة الذاتية لماكس فيبر، ثم تطرقنا إلى طبيعة علم الاجتماع كما يراها فيبر، والتي تستند إلى مجموعة من التصورات، والأفكار، والمفاهيم، والنظريات، وانتقلنا بعدها إلى تقديم قراءة لعلم اجتماع الدين، عند فيبر، مع عرض أهم النتائج المتوصل إليها في الخاتمة.
This research paper sought to present and analyze the religious phenomenon of the German sociologist Max Weber, given that he had studied a group of beliefs and religions, such as: Christianity in his book: The Protestant Ethic and the Spirit of Capitalism, and Judaism in his book: Ancient Judaism, and Hinduism and Buddhism in his book: Hinduism and Buddhism, Confucianism and Taoism in his book entitled: Confucianism and Taoism...etc. We first tried to provide a biography of Max Weber, then we touched on the nature of sociology as seen by Weber, which is based on a set of perceptions, ideas, concepts, and theories, and then we moved to provide a reading of the sociology of religion, according to Weber, with the presentation of the most important results reached in the conclusion.
Keywords: علم الاجتماع الديني -- الحضارات الإنسانية -- السلطة الدينية -- فيبر، ماكس، ت. 1920 م